AI-Driven Social Media Marketing and Purchase Intention: The Roles of Brand Trust, Consumer Citizenship Behaviour, and Digital Participation among Generation Z - Eandhizhai, P. G.; Kavitha, A.; Rajaram, Yuvaraj; Lenin, S.; Priya, E. G. Vishnu (International Review of Management and Marketing, 2026)
Artificial intelligence has become an integral component of modern social media marketing, yet limited empirical evidence exists on how AI-driven strategies influence purchase behaviour among Generation Z consumers. This study aims to examine the impact of AI-driven social media marketing on purchase intention, with the mediating roles of brand trust, consumer citizenship behaviour, and digital participation, and the moderating role of Generation Z orientation. Data were collected from 487 Generation Z consumers in Chennai using a structured questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that AI-driven social media marketing significantly enhances brand trust, consumer citizenship behaviour, and digital participation, which in turn positively influence purchase intention. Consumer citizenship behaviour emerged as the strongest predictor of purchase intention. Generation Z was found to strengthen the effects of AI-driven marketing on behavioural engagement and purchase intention. AI-driven social media marketing plays a crucial role in shaping consumer behaviour by fostering trust, encouraging engagement, and driving purchasing decisions among young digital consumers.